Adjustments in Torque Steadiness During Fatiguing Contractions Are Inversely Correlated With IQ in Persons With Multiple Sclerosis - Gould, Jeffrey R.; Reineberg, Andrew E.; Cleland, Brice T.; Knoblauch, Kristi E.; Clinton, Grace K.; Banich, Marie T.; Corboy, John R.; Enoka, Roger M. (Frontiers in Physiology, 2018)
Fatigue is one of the most debilitating symptoms of multiple sclerosis (MS), and the underlying mechanisms are poorly understood. When exposed to a physical or cognitive challenge, individuals with MS tend to exhibit greater declines in task performance (performance fatigability) and increased levels of self-reported fatigue (perceived fatigability), but these effects may be attenuated by greater intellectual capacity. The purpose of our study was to examine the influence of intelligence on performance fatigability and perceived fatigability in persons with MS. We hypothesized that greater intellectual capacity confers some protection against heightened levels of fatigue and fatigability associated with MS. Twelve adults with relapsing-remitting MS were compared with 12 control (CO) subjects who were matched for age, sex, and premorbid intellectual capacity. Performance fatigability was measured as the decline in maximal voluntary contraction (MVC) torque after 60 isometric contractions (10-s contraction, 5-s rest) performed with the knee extensor muscles. Perceived fatigability was assessed with the modified fatigue impact scale (MFIS) questionnaire (trait fatigability) and the Borg rating of perceived exertion (RPE, state fatigability). Persons with MS reported greater MFIS scores (MS: 43 ± 14; CO: 11 ± 8, P ≤ 0.001). Initial MVC torque for the knee extensors did not differ between the groups (MS: 112 ± 38 N•m; CO: 107 ± 44 N•m) and the decline in MVC torque (performance fatigability) was similar for both groups (MS: -16 ± 19 N•m; CO: -13 ± 16 N•m). RPE increased during the fatiguing contraction for both groups (P < 0.001) but was significantly greater in magnitude (main effect for group, P = 0.03) and increased more for the MS group (group x time interaction, P = 0.05). Torque steadiness declined during the fatiguing contractions (main effect for time, P = 0.05) and was less for the MS group (main effect for group, P = 0.02). Verbal IQ was correlated with the decline in torque steadiness (r = -0.82, P = 0.001). Intellectual capacity was not associated with either performance or perceived fatigability in persons with MS but was associated with adjustments in muscle activation during the fatiguing contractions.